2008
DOI: 10.1016/j.jbiotec.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Generation of engineered recombinant hepatocyte growth factor cleaved and activated by Genenase I

Abstract: Hepatocyte growth factor (HGF) is biosynthesized as a biologically inactive, single-chain form (pro-HGF). Its activation is associated with cleavage at Arg494-Val495 into a two-chain mature form composed of disulfide-linked α-and β-chains. Because serum is a major source of HGF activator (the predominant serine protease responsible for the processing of pro-HGF), serum-free production of recombinant, two-chain HGF had not been established. In this study, to enable serum-free production of two-chain HGF, we gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Since the wild-type HGF undergoes spontaneous cleavage by the action of serum-derived proteases during the protein expression in mammalian cells, we prepared engineered HGF where the cleavage site of wild-type HGF (KQLR/V) was mutated to the recognition sequence of Factor Xa (IEGR/V). Similar engineered HGF was previously reported by introducing the Genenase I cleavage site 18 , but we chose Factor Xa to achieve more controlled and efficient cleavage. This mutant HGF (called HGF(Xa) hereafter) would remain single chain (i.e., scHGF(Xa)) during the biosynthesis and purification but can be converted to an active two-chain species (i.e., tcHGF(Xa)) after the treatment with Factor Xa, exposing a new N-terminus at Val495 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the wild-type HGF undergoes spontaneous cleavage by the action of serum-derived proteases during the protein expression in mammalian cells, we prepared engineered HGF where the cleavage site of wild-type HGF (KQLR/V) was mutated to the recognition sequence of Factor Xa (IEGR/V). Similar engineered HGF was previously reported by introducing the Genenase I cleavage site 18 , but we chose Factor Xa to achieve more controlled and efficient cleavage. This mutant HGF (called HGF(Xa) hereafter) would remain single chain (i.e., scHGF(Xa)) during the biosynthesis and purification but can be converted to an active two-chain species (i.e., tcHGF(Xa)) after the treatment with Factor Xa, exposing a new N-terminus at Val495 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HGF was originally, like platelet‐derived growth factor (PDGF), isolated from platelets and it has been suggested that it is secreted as an inactive single‐chain glycoprotein precursor pro‐HGF 23. The pro‐HGF forms an active heterodimeric peptide consisting of a 69‐kDa α‐chain (HGFα) and a 34‐kDa β‐chain (HGFβ) after being cleaved by a serum serine protease 23, 34. The functional HGF then binds the corresponding receptor, HGF receptor (c‐MET), via β‐chain 35 to stimulate cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Mv1Lu mink lung epithelial cells obtained from RIKEN BioResource Center (Tsukuba, Japan) were used for the cell proliferation assay [46,47]. Mv1Lu cells were cultured in Minimum Essential Medium supplemented with 10% FBS and 1% non-essential amino acids.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%